2017
DOI: 10.3844/ajassp.2017.869.877
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mothers Knowledge Regarding the Developmental Milestone among Children Under Two Years in Iraq

Abstract: Assessing a child's growth through the observation of his/her developmental milestone requires a team effort, in which family plays an important role. To assess the knowledge of the Iraqi mothers regarding their children's developmental milestones of their children and to find out if there was any association between this knowledge and certain demographic variables. A cross sectional study, that extended for one year period with sample size of 400 mothers attending six primary health care centers in Baghadad f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…Four-fifths of the participants received a “poor” score on the overall assessment, as they answered less than 40% of the total questions correctly. It is interesting to note that a similar level of knowledge was reported among Albertan adults [ 8 ], while higher scores were reported among other Arab populations [ 7 , 13 ]. Such differences in results could be related to a variety of reasons.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Four-fifths of the participants received a “poor” score on the overall assessment, as they answered less than 40% of the total questions correctly. It is interesting to note that a similar level of knowledge was reported among Albertan adults [ 8 ], while higher scores were reported among other Arab populations [ 7 , 13 ]. Such differences in results could be related to a variety of reasons.…”
Section: Discussionsupporting
confidence: 58%
“…Most of the existing studies about normal child development focus mainly on mothers [ 4 , 7 , 11 , 13 , 14 ]. In our study, we tried to identify the knowledge gaps of both parents, and we found that mothers are twice as knowledgeable as fathers, which could be related to more frequent contact with their children [ 16 ]; similar gender-related findings were reported in the literature among Western populations [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, though there was no link between the number of children and maternal awareness of ECDM, probably because women in our study had only one or two children, we did, however, finwd a significant association with increasing years of formal education. This was also found in a similar study across different sociocultural settings; in villages of Kanchipuram district, Tamil Nadu [22], and among Saudi mothers in the Middle East [23] as well as areas of conflict like Iraq [24]. It can be expected that a mother with better knowledge regarding development would interact and stimulate the child more to improve the developmental outcome of her child [25,26].…”
Section: Online Firstsupporting
confidence: 64%